Intelligent Resilience in Multi-Cloud Systems (International Journal of Scientific Research in Science and Technology, 2024)
In an era defined by rapid digital transformation, the resilience of cloud infrastructure has become foundational to uninterrupted business operations and user trust. This research presents an evolved framework for cloud resiliency engineering, addressing critical gaps in conventional practices by integrating empirical benchmarking, AI-driven automation, compliance-aware design, and quantum-resilient security protocols. The study explores the challenges and opportunities of building fault-tolerant architectures across multi-cloud, edge, and hybrid ecosystems, while highlighting the importance of human factors, incident response culture, and policy alignment in resilience planning. Through real-world case studies, economic modeling, and interoperability analysis, this work provides a practical and strategic blueprint for organizations seeking to enhance operational continuity, reduce recovery time, and future-proof their digital environments against both known and emerging threats. The findings aim to bridge theory with applied solutions, offering actionable insights for architects, engineers, and enterprise leaders in the cloud ecosystem.
Keywords: Multi-Cloud Resilience; Cloud Automation; Edge Integration; Technical Debt Management; Cloud Incident Response